Application of biochar and organic fertilizer to saline‐alkali soil in the Yellow River Delta: Effects on soil water, salinity, nutrients, and maize yield. (7th June 2022) - Wang, Shibin; Gao, Peiling; Zhang, Qingwen; Shi, Yulong; Guo, Xianglin; Lv, Qingxin; Wu, Wei; Zhang, Xue; Li, Mengzhao; Meng, Qingmei
Abstract: Soil salinization is a global problem that limits agricultural productivity and sustainable development. As waste‐derived soil amendments, biochar and organic fertilizer have garnered considerable attention for their ability to improve soil physicochemical properties and contribution to agricultural waste resource recovery. However, comparable data on the effects of biochar and organic fertilizers on the physicochemical properties of saline‐alkali soils are lacking. Therefore, we applied biochar (B1: 5 t ha −1 year −1 ; B2: 10 t ha −1 year −1 ; and B3: 20 t ha −1 year −1 ) and organic fertilizer (OF1: 7.5 t ha −1 year −1 and OF2: 10 t ha −1 year −1 ) to saline‐alkali soil in the Yellow River Delta (YRD), China, continuously for 3 years. Because of the influence of their application on soil fertility and water‐salt status, maize yield increased by 55.01–62.51% and 15.01–26.67% for the biochar and organic fertilizer treated soils, respectively. Biochar and organic fertilizer increased soil water content, Ca 2+, Mg 2+, total phosphorus, available phosphorus, total nitrogen, NO 3 − ‐N, NH 4 + ‐N, organic matter, and microbial biomass carbon and nitrogen, while decreasing the sodium adsorption ratio and soil pH. Compared with CK, Na + and soil salt content were reduced by 3.83–8.16% and 2.45–12.08%, respectively, under biochar treatments and increased by 2.19–5.34% and 12.95–20.02%, respectively, under organic fertilizer treatments. Principal component analysis showed that biochar was more effective than organic fertilizer in increasing SWC and reducing salinity and Na + . Based on the evidence of this study, biochar presents an eco‐friendly agricultural strategy for improving saline‐alkali soils and increasing maize yield in the YRD.